YVO4:Nd3+ nanophosphors as NIR-to-NIR thermal sensors in wide temperature range. Issue 1 (December 2017) - Kolesnikov, I.; Kalinichev, A.; Kurochkin, M.; Golyeva, E.; Kolesnikov, E.; Kurochkin, A.; Lähderanta, E.; Mikhailov, M.
Abstract We report on the potential application of NIR–to–NIR Nd3+ -doped yttrium vanadate nanoparticles with both emission and excitation operating within biological windows as thermal sensors in 123–873 K temperature range. It was demonstrated that thermal sensing could be based on three temperature dependent luminescence parameters: the luminescence intensity ratio, the spectral line position and the line bandwidth. Advantages and limitations of each sensing parameter as well as thermal sensitivity and thermal uncertainty were calculated and discussed. The influence of Nd3+ doping concentration on the sensitivity of luminescent thermometers was also studied.